Tenants’ satisfaction in high residential buildings / Ummu Sholehah Mohd Nor, Wan Nor Azriyati Wan Abd Aziz and Zafirah Al Sadat Zyed. - Mohd Nor, Ummu Sholehah; Wan Abd Aziz, Wan Nor Azriyati; Al Sadat Zyed, Zafirah (Faculty of Architecture, Planning and Surveying (FSPU) and UiTM Press Universiti Teknologi MARA (UiTM), Selangor, Malaysia., 2020)
High residential living in Malaysia has not been widely given a significant emphasises in literature despite its increasing scale and significance in the real estate market. The significance of high rise is commonly due the increasing rate of migration from rural to urban. It is estimated a total of 77.2 percent of the Malaysian population lived in urban areas in 2020. Approximately, 30 percent of this urban population lives in strata housing. These percentages are predicted to continue to increase in the future. The emergence of high residential building has been argued as confronting various problems which has considerable impact on this life style. Satisfaction is an important outcome of living in one’s dwelling, although it is not the only consideration. High residential buildings (HRB) in Malaysia encountered numerous problems in term of management aspects, legislation aspects, and residents’ satisfaction. The purpose of this paper is to investigate the tenants’ satisfaction living in HRB in Klang Valley. The face-to-face interview is conducted amongst 276 tenants at low cost and medium cost HRB using non-parametric convenience sampling. The result from this study indicates that tenant in medium cost high residential buildings (HRB) are more satisfied in term of management and facilities as compared to tenants in low cost HRB. Tenants also not disclosed to the existing act and procedure related to HRB. In conclusion, this study suggested the Local Authority to emphasise the role of tenant. These recommendations hopefully will increase the level of satisfaction amongst the residents in HRB.